Distribution, diversity, and specificity of a parasitic algal genus Cephaleuros in Thailand - Wikrom Chanthapatchot,; Anchittha Satjarak, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Cephaleuros has been recognized as a terrestrial parasitic green algal genus causing algal red rust diseases which have violently damaged economic crops worldwide. To obtain information of the algal distribution in Thailand and to understand the specificity of the algal parasite and their hosts, we reviewed the reports on this algal genus in Thailand and performed comparative analyses of the algal-host specificity. Results indicated that more than 10 species of Cephaleuros have been reported across Thailand. Their presence varies from regions to regions with the highest numbers of reports from the southern part of Thailand. The leaf area of infection also varied due to the different algal infecting mechanisms. We found that C. annonae, C. drouetii, C. henningsii, C. lagerheimii, C. parasiticus, C. pilosa, C. piperis and C. solutus appeared to be specific to plant family while C. diffusus, C. expansa, C. karstenii, C. tumidae-setae and C. virescens infected wider range of plant species. Among these, C. virescens had the highest number of reports as it was present in all the regions of Thailand where it infected various plant species belonging to more than 20 plant families. Analyses of C. virescens suggested the presence of putative sequence of gene encoding a virulence protein in this alga. The information on the distribution and algal-host specificity might help in understanding the spread of this red rust plant disease due to the algal genus Cephaleuros in Thai economic plants.